Obstetrics obstacles: a focus on social obstetrics of Bangladesh - Banu, Nasreen; Ferdoush, Jannatul; Begum, Tahera (Bangladesh Medical Journal, 2016)
Abstract not available Bangladesh Med J. 2015 Jan; 44 (1): 57